1981
DOI: 10.1111/j.1399-3054.1981.tb02729.x
|View full text |Cite
|
Sign up to set email alerts
|

Brassinolide, a growth‐promoting steroidal lactone

Abstract: Brassinolide (BR), a naturally‐occurring‐steroidal lactone from rape (Brassica napus L.) pollen, was compared with auxin for activity in a number of bioassay systems. Responses similar to IAA were elicited by BR in bioassays based upon bean hypocotyl hook opening, elongation of maize mesocotyl, pea epicotyl and azuki bean epicotyl sections, and fresh weight increase in Jerusalem artichoke (2,4‐D used) and pea epicotyl sections. The azuki bean and dwarf pea epicotyl bioassays were much more responsive to BR tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
1
4

Year Published

1983
1983
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 32 publications
4
63
1
4
Order By: Relevance
“…Like auxin, BR has pronounced effects on the elongation of stem tissue. Maize mesocotyls, pea, Azuki bean, and mung bean epicotyls (9,13,30), bean and cucumber hypocotyls (12,14), and wheat coleoptiles (23) all respond to submicromolar concentrations of BR by elongating. It has been suggested that the effects of BR are mediated through auxin or that BR increases tissue sensitivity to endogenous auxins (13).…”
mentioning
confidence: 99%
“…Like auxin, BR has pronounced effects on the elongation of stem tissue. Maize mesocotyls, pea, Azuki bean, and mung bean epicotyls (9,13,30), bean and cucumber hypocotyls (12,14), and wheat coleoptiles (23) all respond to submicromolar concentrations of BR by elongating. It has been suggested that the effects of BR are mediated through auxin or that BR increases tissue sensitivity to endogenous auxins (13).…”
mentioning
confidence: 99%
“…(13) and needles of spruce (14). Because IAA appears to play an important role in the regulation of cambial activity in woody plants (6), and BR is known to interact synergistically with IAA (1,3,8,10,16,17), we looked for BRs in scrapings ofthe cambial region of Scots pine (Pinus silvestris) harvested during the cambial growing period. In the process, we also developed a sensitive and simple dwarfrice lamina inclination bioassay based on the intact seedling assay of Takeno and Pharis (10).…”
mentioning
confidence: 99%
“…It also means that the membrane potential reflects proton pumping more sensitively than medium acidification does, thereby allowing a discrimination with respect to the potency of the substances (no unambiguous effect of stigmasterol on the membrane potential in the light, in the dark occasionally hyperpolarization of transient character). These results suggest the existence ofa mechanism ofaction brought about by steroids on proton pumping that varies from that of IAA (15) and FC, respectively. The reasons for this are: (a) in contrast to FC, the effect of the steroids on the membrane potential and on medium acidification is reversible; and (b) SSHB significantly stimulated FeCN reduction also in the light.…”
Section: Discussionmentioning
confidence: 76%
“…Egeria leaves (10)(11)(12)(13)(14)(15) were incubated for 1 h in 2 mL of a solution containing 4 nm (reference 500 nm). The experiments were peformed at least three times with five replicates.…”
Section: Reduction Of Fecnmentioning
confidence: 99%